PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN TENTANG PENCEGAHAN KOMPLIKASI PENYAKIT HIPERTENSI DI DESA GAREN PANDEYAN NGEMPLAK BOYOLALI - Winarno, Syidiq; Sani, Fahrudin Nasrul; Utomo, Endrat Kartiko (Jurnal Keperawatan Duta Medika, 2024)
Introduction: Hypertension is a condition of systolic blood pressure of more than 140 mmHg or diastolic blood pressure of more than 90 mmHg, which is measured twice with an interval of five minutes and in a condition of adequate rest and calm. Blood pressure is a description of a person's hemodynamic situation at a certain time, hemodynamics is a condition in which pressure and blood flow can maintain the exchange or perfusion of substances in tissues. The purpose of health education is to increase the knowledge of respondents. With the increase in respondents' knowledge, there is a change in attitude towards adaptive in accordance with the information obtained through health counseling. Objective: This study is to determine the effect of health education on the level of knowledge about the prevention of complications of hypertension in Garen Pandeyan Ngemplak Boyolali Village. Method: the research used is quantitative research with analytical correlation with Quasi-Experimental method with pre-test and post-test approaches one group control only. Data from this study was obtained from filling out questionnaires that had been tested for validity and reliability and analyzed using the Wilcoxon Signed Ranks Level Test before health education was carried out knowledge about preventing complications of hypertension, the average level of knowledge of 73 respondents was 5.94 with a minimum of 3 points and a maximum of 9 points. The level of knowledge after the implementation of health education, retrieval of knowledge data on the prevention of complications of hypertension was carried out. Results: The results of the study obtained an average level of knowledge from 73 respondents with post-test result criteria 7 with a minimum score of 6 points and a maximum of 10 points. Conclusion: Based on the results of the study, there is a significant difference between the level of . Keywords: health education, leve of knowledge, complications of hypertension